Unlocking dairy traceability: Current trends, applications, and future opportunities - Mohit Malik; Vijay Kumar Gahlawat; Rahul S Mor; Manish Kumar Singh (Future Foods)
Traceability is a transparent quality index in almost every supply chain. Especially when it comes to highly perishable products, such as dairy, the need for an effective traceability system is unavoidable due to increased fraudulent products, adulteration, excessive additives, and toxic substances. The dairy industry requires an effective traceability system that ensures visibility and transparency in the supply chain while enhancing safety, quality, and adherence to ethical standards; promotes consumer trust and stakeholder collaborations; optimizes dairy operations for economic benefits; and enables end-to-end tracking and monitoring of processes. By effectively utilizing resources and reducing wastage, the system supports the principal objectives of sustainable development through advancing reliability and constant advancements. This paper offers insights into the recent developments, trends, opportunities, and impacts of traceability implementation in the dairy industry. The theoretical and technological status of traceability was investigated, and the content analysis was used to examine the intervention of digital technologies in dairy traceability and sustainability indicators. The study highlights research indicators in different dairy domains, suggesting potential traceability research pathways. It also discusses past, present, and future aspects of traceability, along with challenges, advancements through digital technologies, and its implications for dairy stakeholders. The findings revealed that implementing an effective traceability system can help attain specific United Nations Sustainable Development Goals (UN SDGs).